What Universities Can Be: A New Model for Preparing Students for Active Concerned Citizenship and Ethical Leadership: by Robert J. Sternberg. Ithaca, NY: Cornell University Press, 2016. 279 pp. Issue 2 (3rd April 2017) - Andersen, Kent
Abstract: Sternberg's What Universities Can Be provides a thorough and thought-provoking consideration of how to prepare students to ACCEL, an acronym for active concerned citizenship and ethical leadership. Sternberg considers all aspects of an institution, including admissions, student learning outcomes, assessment, faculty reward structures, and marketing. Of particular interest are Sternberg's arguments for developing practical intelligence and ethical reasoning, as well as examples of alternative admissions tests. This review summarizes and contextualizes Sternberg's key arguments.